DEVELOPMENT OF COMPETENCE (METHODOLOGY) OF FUTURE PRIMARY SCHOOL STUDENTS IN USING STEAM TECHNOLOGIES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
This article investigates the development of competence in utilizing Science, Technology, Engineering, Arts, and Mathematics (STEAM) technologies among future primary school students. The methodology employed focuses on innovative approaches to foster a well-rounded skill set that goes beyond traditional educational paradigms. Through a combination of hands-on activities, collaborative learning, and interactive experiences, the study aims to enhance the students' proficiency in leveraging STEAM technologies. The article also addresses the pedagogical considerations and challenges associated with implementing such methodologies in primary education.